Acute Toxicity Test Of The Green Viper Snake (Trimeresurus albolabris), Macroscopic Description Of The Kidney And Liver Of Mice (Mus musculus) - Darmawan, Moch. Rizky; Rahardjo, Dadik; Tyasningsih, Wiwiek; Kurnijasanti, Rochmah; Legowo, Djoko; Setiawan, Boedi (Universitas Airlangga, 2021)
According to WHO (2010), the Trimeresurus albolabris snake is a venomous snake with a high number of bite cases in Indonesia. Information on the character and level of toxicity of snake venom in Indonesia, including Trimeresurus spp. snakes, is still minimal. This study aims to determine the LD50 value (lethal dose 50), clinical symptoms, and to determine the macroscopic appearance of the liver and kidneys of mice (Mus musculus) after being injected by a the white-lipped pit viper (Trimeresurus albolabris) venom. The LD50 value of Trimeresurus albolabris venom injected subcutaneously into mice was 5,09 mg/kgBW. Clinical symptoms that appear increased movement activity, increased respiratory rate, lethargy, decreased activity, and reduced grooming. Macroscopic appearance of the liver that looks abnormal is found (1) color changes in the form of pale, pale yellowish, and red spots (petechiae). (2) changes in surface structure found only one liver that is not flat. (3) changes in consistency in the form of brittle easily. In the kidney that looks abnormal, found (1) changes in color in the form of pale. (2) changes in surface structure were only found in one kidney in the form of nodules. (3) changes in consistency in the form of brittle easily and soft.